The Knockout for G Protein-Coupled Receptor-Like PfSR25 Increases the Susceptibility of Malaria Parasites to the Antimalarials Lumefantrine and Piperaquine but Not to Medicine for Malaria Venture Compounds - Santos, Benedito M.; Dias, Bárbara K. M.; Nakabashi, Myna; Garcia, Celia R. S. (Frontiers in Microbiology, 2021)
Previously we have reported that the G protein-coupled receptor (GPCR)-like PfSR25 in Plasmodium falciparum is a potassium (K+) sensor linked to intracellular calcium signaling and that knockout parasites (PfSR25-) are more susceptible to oxidative stress and antimalarial compounds. Here, we explore the potential role of PfSR25 in susceptibility to the antimalarial compounds atovaquone, chloroquine, dihydroartemisinin, lumefantrine, mefloquine, piperaquine, primaquine, and pyrimethamine and the Medicine for Malaria Venture (MMV) compounds previously described to act on egress/invasion (MMV006429, MMV396715, MMV019127, MMV665874, MMV665878, MMV665785, and MMV66583) through comparative assays with PfSR25- and 3D7 parasite strains, using flow cytometry assays. The IC50 and IC90 results show that lumefantrine and piperaquine have greater activity on the PfSR25- parasite strain when compared to 3D7. For MMV compounds, we found no differences between the strains except for the compound MMV665831, which we used to investigate the store-operated calcium entry (SOCE) mechanism. The results suggest that PfSR25 may be involved in the mechanism of action of the antimalarials lumefantrine and piperaquine. Our data clearly show that MMV665831 does not affect calcium entry in parasites after we depleted their internal calcium pools with thapsigargin. The results demonstrated here shed light on new possibilities on the antimalarial mechanism, bringing evidence of the involvement of the GPCR-like PfSR25.